Symmetry and Complexity 2019 - Cattani, Carlo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Symmetry and complexity are studied by a selection of outstanding papers ranging from pure Mathematics and Physics to Computer Science and Engineering applications. In this Special Issue, the authors give a short but intensive description of the many applications of the basic structure of symmetry and complexity in many fields. Some interesting results were given in the Hydrodynamic Analysis of 3-D Hydrofoil and Marine Propeller and in the SAT Problems. The Study on Hypergraph Representations of Complex Fuzzy Information shows the importance of methods based on symmetry and complexity. A deep study of Information Technology Services in Public Organizations has been given in this issue, together with some interesting papers dealing with Adaptive Block Truncation Coding Based on an Edge-Based Quantization, SIR Model in a Patchy Environment, and the Evolution of Conformity Dynamics in Complex Social Networks. Another interesting paper provides some new insights into the Novel Computational Technique for Impulsive Fractional Differential Equations. In this collection, An Intelligent Approach for Handling Complexity by Migrating from Conventional Databases to Big Data shows the importance of such topics related to complexity.